The unequal effects of resettlement in Coastal Regions: An intersectional vulnerability analysis of resettled fisher communities in Saint Louis, Senegal - Renkamp, Theresa Marie; Reine, Hane Marie; Jaquet, Stéphanie; Medina, Leonardo; Bonatti, Michelle; Sieber, Stefan (Elsevier, 2025)
The coast of West Africa is particularly affected by coastal erosion and inundation as a result of sea-level rise. Managed resettlement has emerged as a crucial adaptation strategy for vulnerable coastal communities. However, the retreat of fisher communities and unequal resettlement outcomes in the Global South remain under-researched. This study seeks to examine how the vulnerability of various groups within fisher communities has evolved following their resettlement inland. Given the highly gendered division of labour in fishery-based livelihoods – and its effects on intra-household and community power relations – a contextually grounded vulnerability analysis must consider not only livelihood provision but also reproductive labour and structural causes of vulnerability. For this, the study applies a framework informed by feminist political ecology and intersectionality. A comparative case study analysis of resettled fisherfolks in Saint Louis, Senegal, was conducted through a mixed method approach, including a quantitative survey (n = 115), focus group discussions, and participatory mapping exercises. An intersectional analysis was conducted across social groups defined by location, gender, age, marital status, wives’ position, and household status. An increase in vulnerability was observed followingresettlement due to everyday struggles in providing livelihood, precarious living conditions affecting social reproductive work, and exposure to gender-based violence and criminality within the resettlement. As the adaptive capacity of certain groups, including young unmarried individuals and women, was especially diminished due to social isolation, limited agency and work opportunities, the resettlement increased marginalisation. Overall, the study shows that mismanagement of resettlement projects can lead to maladaptation. A successful resettlement necessitates a balanced, context-specific approach, combining immediate recovery efforts with strategic, long-term planning, and acknowledging communities' livelihood traditions as well as intersectional vulnerabilities.